A companion to Anabaptism and spiritualism, 1521 - 1700 - Roth, John D.; Stayer, James M. (Brill's companions to the Christian tradition, 2007)
Karlstadt, Müntzer, and the Reformation of the commoners, 1521-1525 / Hans-Jürgen Goertz -- Swiss Anabaptism: the beginnings, 1523-1525 / C. Arnold Snyder -- Swiss-south German Anabaptism, 1526-1540 / James M. Stayer -- Spritualism: Schwenckfeld and Franck and their early modern resonances / Emmet McLaughlin -- Anabaptism in Moravia and Silesia / Martin Rothkegel -- The Melchiorites and Münster / Ralf Klötzer -- The spiritualist Anabaptists / Geoffrey Dipple -- Mennonites and Doopsgezinden in the Netherlands, 1535-1700 / Piet Visser -- Marpeck and later Swiss Brethren, 1540-1700 / John D. Roth -- Anabaptist religious literature and hymnody / John Rempel -- Gender roles and perspectives among Anabaptist and spiritualist groups / Sigrun Haude -- Anabaptist martyrdom : imperatives, experience, and memorialization / Brad S. Gregory -- Anabaptists and the early modern state / Michael Driedger